Integrated Disaster Management: an Arena for Interstate Cooperation Amongst State in India. - Sabhlok, Anu (2009)
The paper presents an argument for increased cooperation amongst states in India for the purpose of effective and integrated disaster management. Disasters do not recognise political boundaries and even when they are localised, their after-effects spill over to other states in the Union. Various mutually beneficial reasons for the states to develop a cooperative approach towards disaster management are discussed here, besides the possible deterrents to such cooperation. Using the United States’ Emergency Management Assistance Compact, the working mechanism for integrated disaster management is reflected upon. Towards the end, some approaches that could be adopted for developing an efficient disaster management system in India have been suggested